Inelastic velocity ratio: Acceleration and non-acceleration pulses - Durucan, Ayse rusen; Durucan, Cengizhan (Elsevier Science Inc, 2025)
This study aims to illustrate the potential differences in the inelastic velocity ratios of forward-directivity velocity pulse-type ground motion records: (i) those with acceleration pulses and (ii) those without. Recent studies have shown that acceleration pulses in forward-directivity velocity pulse-type ground motion records may impose different demands on structures compared to records without these pulses. This study investigates these potential differences in terms of the inelastic velocity ratio, which can serve as a design tool within the performance-based earthquake engineering framework. Numerous linear and nonlinear analyses were conducted using 119 ground motion records, also employed in a recent study to evaluate the results. The findings reveal that the presence of acceleration pulses can alter the inelastic velocity ratio values, indicating the need to treat such records separately from those without acceleration pulses. Furthermore, the study underscores the potential benefits of using a truncated structural period range (as opposed to a wider range) to simplify the form of prediction equations and enhance their accuracy.
Keywords: Nonlinear time history analyses; Velocity pulses; Acceleration pulses; Ground motion records